2018
DOI: 10.1111/jfbc.12737
|View full text |Cite
|
Sign up to set email alerts
|

Histochemistry, phenolic content, antioxidant, and anti-diabetic activities ofVernonia amygdalinaleaf extract

Abstract: Vernonia amygdalina leaves were investigated for their histochemical properties and antidiabetic activities. Histochemical analysis of the leaf revealed distributions of acidic lipid, mucilage, and pectin, lipids, polyphenols, and alkaloids at the mid rib, glandular trichome, and epidermis. HPLC analysis of the leaves hot water infusion revealed the presence of quercetin and (‐)‐epi‐catechin. The infusion had significant (p < 0.05) 2,2′‐diphenyl‐1‐picrylhydrazyl scavenging activity and ferric reducing antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 61 publications
3
17
0
Order By: Relevance
“…In conclusion VA has an ability to increase endogen antioxidant including SOD. Another previous research reported that VA had an ability to increase endogen antioxidant (Glutathione and Superoxide dismutase) [49].…”
Section: Cardiac Antioxidantmentioning
confidence: 88%
“…In conclusion VA has an ability to increase endogen antioxidant including SOD. Another previous research reported that VA had an ability to increase endogen antioxidant (Glutathione and Superoxide dismutase) [49].…”
Section: Cardiac Antioxidantmentioning
confidence: 88%
“…Flavonoids are phenolic substances with many health properties that frequently exhibit inhibitory effects against alpha-glucosidase enzymes [ 19 ]. In general, although previous studies reported on luteolin and its pharmacological activity [ 20 , 21 , 22 ], more analyses are performed on the leaves than the flower. Furthermore, four compounds that are reported to be isolated from flower extracts are tricosane, vernolide, isorhamnetin, and luteolin [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The plant is used in traditional medicine for the treatment of a variety of ailments, including malaria [12]. An antidiabetic effect of VA was reported by Erukainure et al [13], while Okunlola et al [14] gave a report of its antioxidant properties. Additionally, its anticancer property has been reported [15].…”
Section: Introductionmentioning
confidence: 99%